Peningkatan Wawasan Kebangsaan Peserta Didik Melalui Media Pembelajaran Berbasis Game Based Learning Educaplay - Aura Sabrina Malika; Dadang Sundawa; Rika Sartika (LPPM Institut Pendidikan Nusantara Global, 2026)
The teaching of Pancasila and Civic Education (PPKn) currently still faces challenges in internalizing national values due to the dominance of conventional methods that tend to be monotonous and memorization-oriented. This study aims to analyze the effectiveness of using Game-Based Learning (GBL)-based instructional media through the Educaplay in enhancing students’ national awareness. The research method employed was a quantitative approach with a quasi- experimental design (Nonequivalent Control Group Design) involving an experimental class and a control class at Angkasa Husein Sastranegara High School in Bandung. The results of the study indicate a significant increase in national awareness in the experimental class, with the average score rising from 51.22 to 89.22, far surpassing the control class, which only reached 74.06 from 66.218. The N-Gain analysis reinforced these findings, with 77.42% of students in the experimental class achieving the high improvement category, while the majority of the control class fell into the low category at 71.87%. In conclusion, the use of the Educaplay platform proved to be more effective than conventional methods in enhancing students’ national awareness. This approach provides an interactive, multimodal learning experience relevant to the characteristics of Generation Z, thereby effectively reducing cognitive load and increasing student engagement.